Liquidity constraints of the middle class - Jeffrey R. Campbell; Zvi Hercowitz (Federal Reserve Bank of Chicago, 2009)
The consumption of households with liquid financial assets responds much more to transitory income shocks than the permanent-income hypothesis predicts. That is, middle class households with assets act as if they face liquidity constraints. This paper addresses this puzzling observation with a model of impatient households that face a large recurring expenditure. In spite of impatience, they save as this expenditure draws near. We call such saving made in preparation for a foreseeable event at a given future date term saving. Term saving reverses the role of assets in the presence of liquidity constraints. Typically, assets grow following past lucky events; thus assets imply an abundance of liquidity. Here, assets indicate an impending need for funds and a shortage of liquidity. The borrowing constraint will bind at the time of the expenditure, and assets will then be zero. This separates planning up to that time from the rest of the household's lifetime and thereby shortens its effective horizon. Intertemporal substitution over a limited period generates a strong consumption response to temporary income changes. As the expenditure approaches, the effective horizon shortens further and the household accumulates assets. Hence, households with more assets have larger consumption responses. We compare a calibrated version of the model with observations from the 2001 U.S. tax rebate and with evidence on excess smoothness and persistence of aggregate consumption.
Keywords: E21; 330; Fiscal Policy; Tax Rebates; Marginal Propensity to Consume; Term Saving